Hong Kong Students Consider Virtual Reference a Vital Service and It Can Aid in Many Stages of Learning / Tsang, A. L. Y., & Chiu, D. K. W. (2022). Effectiveness of virtual reference services in academic libraries: A qualitative study based on the 5E learning model. The Journal of Academic Librarianship, 48(4), Article 102533. https://doi.org/10.1016/j.acalib.2022.102533 - Kaplan, Samantha J. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – Understand how virtual reference services (VRS) impact students’ learning using the 5E model (engage, explore, explain, elaborate, evaluate) as a theoretical framework.Design – Exploratory qualitative study.Setting – Major university in Hong Kong.Subjects – There were 10 participants between the ages of 18 and 35, including undergraduate and postgraduate students and one alumnus of the university.Methods – Online synchronous semi-structured interviews of 30 minutes via Zoom. Interview data were transcribed and analyzed thematically according to the 5E learning model.Main Results – WhatsApp was the preferred form of VRS, over Zoom, email, or phone. VRS can facilitate better awareness of library resources and supports resource exploration. WhatsApp VRS is particularly valuable for students who may find other modes intimidating, overly formal, or inaccessible due to time constraints. VRS has grown in importance since the COVID-19 pandemic.Conclusion – VRS provided via instant messaging is a valued service for students, but libraries, library websites, and librarians can all work to improve awareness of the option and possible uses. Future work is needed to understand how demographics may influence patrons’ attitudes and experiences of VRS.